Analisis Buku Bahasa Arab Tingkat MPDM Muhammadiyah - Primasti Nur Yusrin Hidayanti; Mirwan Akhmad Taufiq; Faris Maturedy (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
In the learning process, learning resources are one of the main components used to achieve learning objectives. One of the learning resources is the use of teaching materials books. The teaching materials used in the learning process should meet the criteria set by the government so that the resulting learning process will be of high quality. Therefore, this study was conducted to determine the appropriateness of the content of teaching materials from the Arabic-book Al-Ashri class 6 at Madrasah Ibtidaiyyah level with the provisions of the 2013 curriculum. This study uses the library research method using applied content analysis techniques and Al-Ashri Arabic books as the primary source of research. The results of this study state that the teaching materials for the Arabic book Al-Ahsri for grade 6 at the Madrasah Ibtidaiyyah printed by MPDM Muhammadiyah are following the 2013 curriculum with the category of teaching materials suitable for use in the Arabic learning process. However, on the other hand, the authors also find a few shortcomings in the book. Among others, the use of library sources and cultural elements in the themes presented.